Epidemiology, risk factors and prognosis of cardiovascular disease in the Coronavirus Disease 2019 (COVID-19) pandemic era: a systematic review - Pepera, Garyfallia; Tribali, Marina-Sofia; Batalik, Ladislav; Petrov, Ivo; Papathanasiou, Jannis (Reviews in cardiovascular medicine, 2022)
BACKGROUND: Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from China, the novel coronavirus disease 2019 (COVID-19) has caused more than five milion deaths worldwide. Several studies have elucidated the role of risk factors in the prognosis of cardiovascular disease (CVD) in the progression of COVID-19 pandemic. This systematic review assesses the link between COVID-19 and cardiovascular risk factors, and investigates the prognosis in the case of myocardial injury. METHODS: A literature search was performed to identify relevant articles in Pubmed, MEDLINE, Elsevier, and Google Scholar the last two years using the terms: COVID-19, CVD, risk factors, cardiovascular risk factors, SARS-CoV-2, lockdown, hypertension, and diabetes mellitus. Exclusion criteria were the studies associated with pediatric and pregnant COVID-19 patients. RESULTS: After screening through 3071 articles, 10 studies were included in this review that captured the findings from 3912 participants. Included studies found that preexisting CVD was linked to worse outcomes and increased risk of death in patients with COVID-19, whereas COVID-19 itself also induced myocardial injury, arrhythmia, acute coronary syndrome, and venous thromboembolism. CONCLUSIONS: Cardiovascular risk factors such as hypertension, diabetes mellitus, and obesity were associated with intensive care unit admission and poor prognosis. Cardiovascular risk factors are crucial for the progression of COVID-19, and infected patients should be constantly monitored and follow strict hygiene and decrease their social interactions.
Keywords: pandemie; kardiovaskulární nemoci; kontrola infekčních nemocí; Humans; Cardiovascular risk factors; dítě; Child; Communicable Disease Control; rizikové faktory; Pandemics; Systematic review; lidé; Epidemiology; Coronavirus disease pandemic; Cardiovascular disease; COVID-19; Cardiovascular Diseases; Risk factors; prognóza; SARS-CoV-2; Prognosis; Risk Factors